Pembuatan Aplikasi Pengelolaan Nilai Dan Kategorisasi Hasil Akhir Yang Bersifat Fleksibel Terhadap Lingkungan Aplikasinya - Eliezer Mangoting Rongre; Ottopianus Mellolo; Herry Setiawan Langi; Jusuf Luther Mapadang (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
A research has been done titled Making Application To Manage And Categorize The Score That Is Flexible To Any Application Zone.The background of the problem of this research is the need for a application program that is flexsible to be used for many kind of scoring system. .The research began with surveying many scoring system, then design a manual system allowed to modified easily to meet the need of many scoring system. Next the manual syatem converted into an algorithm.The algorithm then be used as basis fo meaking application programe campatibly .. The application program then tested by compating it with manual sytem. The result of of the testing show that the program result is same as result by manual system.A research has been done titled Making Application To Manage And Categorize The Score That Is Flexible To Any Application Zone.The background of the problem of this research is the need for a application program that is flexsible to be used for many kind of scoring system. .The research began with surveying many scoring system, then design a manual system allowed to modified easily to meet the need of many scoring system. Next the manual syatem converted into an algorithm.The algorithm then be used as basis fo meaking application programe campatibly .. The application program then tested by compating it with manual sytem. The result of of the testing show that the program result is same as result by manual system.